Mechanisms facilitating uptake of carboxyl-polyethylene glycol-functionalised gold nanoparticles into multicellular spheroids - Cordier, Werner (University of Pretoria, 2021)
Disseration (MSc (Pharmacology))--University of Pretoria, 2021.